PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO ANIMASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PEMANASAN GLOBAL KELAS X IPA SMA NEGERI 9 KUPANG - Oktovianus Leba; Moses K. Tokan; Arini Rahma Dhani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The Problem Based Learning (PBL) model is a problem-based learning that trains activeness, critical thinking, and problem-solving skills through educational interactions. This study aims to improve motivation and learning outcomes of Global Warming material for class X IPA students of SMA Negeri 9 Kupang through the PBL model assisted by animated videos. This type of research is Classroom Action Research which is carried out in two cycles, including the stages of planning, implementation, observation, and reflection. The research subjects were 20 students with data collection techniques in the form of observation, tests, and questionnaires. The results of the study showed a significant increase in cycle II. The average value of student learning outcomes increased with a completeness level reaching 90%. Student learning activities also increased to 92.85%, where the researcher's activities in both cycles were categorized as successful. Student learning motivation increased from 76.31% in cycle I to 87.75% in cycle II. It was concluded that the application of the Problem Based Learning model assisted by animated videos effectively increased student motivation and learning outcomes on global warming material at SMA Negeri 9 Kupang.